Does ASEAN Matter? A Book Review - Mohamad Rosyidin (Indonesian Perspective, 2019)
There have been abundant scholarly arguments regarding ASEAN and its role in managing interstate relations in Southeast Asia and beyond. This book offers a different perspective based on experience of former Indonesia’s foreign minister. There is no theoretical framework employed by the author to frame his arguments. His arguments are expressed narratively supported by rich empirical data gathered mostly through first-hand or primary sources.